FRACTURE OF AN EXETER„¢ V40„¢ STEM THROUGH THE INSERTION GUIDE HOLE AND REVISION USING CEMENT-IN-CEMENT TECHNIQUE - Onafowokan, Oluwatobi O; Singh, Amit; Patel, Kuntal (Journal of Ayub Medical College Abbottabad, 2022)
Fracture of the Exeter„¢ V40„¢ stem is uncommonly reported in the literature. The cement-in-cement femoral revision is a described technique for revising well-cemented femoral components during revision hip arthroplasty. We present our experience using this technique in managing a fractured Exeter„¢ V40„¢ stem. There have been 24 reported Exeter„¢ V40„¢ stem fractures: 12 at the body and 12 at the neck. 3 of the reported fracture at the neck cases have occurred at the superior aspect of the neck-shaft junction which is an unusual site for failure of this stem. Our patient's fracture pattern matches this unusual presentation. This report has added to the limited evidence indicating the area around the insertion guide hole as a potential site through which stem fracture may begin and propagate inferiorly. The cement-in-cement technique may be successfully employed in managing Exeter„¢ V40„¢ stem fractures, without need for extended trochanteric osteotomy or cortical window.